2021
DOI: 10.1097/shk.0000000000001735
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Pro-inflammatory Cytokines and Their Correlation with Disease Severity and Blood Coagulation in Septic Patients with Bacterial Co-infection

Abstract: To evaluate the clinical significance of pro-inflammatory cytokines for disease severity and coagulation in septic patients with bacterial co-infection. Methods: A total of 92 patients with sepsis admitted to intensive care unit (ICU) from January 2017 to August 2020 were enrolled and their clinical data were retrospectively analyzed. Fortyseven patients (51.1%) had a single infection by Klebsiella pneumoniae or Acinetobacter baumannii (single-infection group), and 45 patients (48.9%) were infected by both spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…DD increases in patients after infection [19,20]. Elevated DD correlated with high levels of CRP, TNFα, and IL-6 after bacterial infection and resulted in adverse outcomes [8,21]. Bacterial elements, such as endotoxin, stimulate the inflammatory response via activation of cytokine-mediated procoagulant effects on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…DD increases in patients after infection [19,20]. Elevated DD correlated with high levels of CRP, TNFα, and IL-6 after bacterial infection and resulted in adverse outcomes [8,21]. Bacterial elements, such as endotoxin, stimulate the inflammatory response via activation of cytokine-mediated procoagulant effects on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's kidney functions gradually recovered and RRT was discontinued on the 25th day. Like COVID-19 infection, inflammatory mediators play an important role in sepsis and septic shock, exacerbating organ damage and correlating with disease severity ( 64 ). Many clinical strategies have been attempted to reduce inflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective emergency department cohort study reported that compared to patients with abnormal D-dimer levels, patients with normal D-dimer levels presented a lower risk of 30-day mortality (18). Furthermore, the increased D-dimer levels were associated with higher production of TNF-α, IL-6, and IL-8 (19,20) and indicated the activation of coagulation and fibrinolysis to develop to disseminated intravascular coagulation (DIC), especially in sepsis (20). All the undesirable biological processes may significantly increase the incidence of multi-system organ failure (MOF) (19), leading to high in-hospital mortality of critically ill children.…”
Section: Discussionmentioning
confidence: 99%